Real-world outdoor air exposure effects in a model of the human airway epithelium – A comparison of healthy and asthmatic individuals using a mobile laboratory setting - Pavel Rossner; Helena Libalova; Tereza Cervena; Michal Sima; Zuzana Simova; Kristyna Vrbova; Antonin Ambroz; Zuzana Novakova; Fatima Elzeinova; Anezka Vimrova; Lubos Dittrich; Michal Vojtisek; et al. (Ecotoxicology and Environmental Safety)
We developed a mobile laboratory allowing field exposure of lung tissue models to ambient air at localities with various pollution sources (Background, Industrial, Traffic, Urban) in different seasons (summer/fall/winter). In samples originating from healthy and asthmatic individuals, we assessed the parameters of toxicity, lipid peroxidation and immune response; we further performed comprehensive monitoring of air pollutants at sampling sites. We measured lactate dehydrogenase (LDH) and adenylate kinase (AK) production and transepithelial electrical resistance (TEER), analyzed 15-F2t-isopostane (IsoP) and a panel of 20 cytokines/chemokines/growth factors. In the ambient air, we detected particulate matter (PM), and other relevant chemicals (benzene, benzo[a]pyrene (BaP), NOx). In the Traffic locality, we found very high concentrations of ultrafine particles and NOx and observed low TEER values in the exposed samples, indicating significant traffic-related toxicity of the ambient air. In the Urban locality, sampled in winter, we observed high PM and BaP levels. We found lower AK levels in samples from healthy individuals exposed in this locality than in the asthmatic samples. In the samples from the Industrial locality, sampled in summer, we detected higher concentrations of TNFα, MIP-1α, Eotaxin, GROα, GM-CSF, IL-6 and IL-7 than in the Urban locality samples. We hypothesize that pollen or other plant-related components of the ambient air were responsible for this response. In conclusion, our data proved the feasibility of our mobile laboratory for field measurements of the biological response of lung tissue models exposed to ambient air, reflecting not only the levels of toxic compounds, but also season-specific parameters.